Protective effect of curcumin on cyclosporin A-induced endothelial dysfunction, antioxidant capacity, and oxidative damage. (May 2014) - Sagiroglu, Tamer; Kanter, Mehmet; Yagci, Mehmet Ali; Sezer, Atakan; Erboga, Mustafa
Cyclosporin A (CsA) is the most widely used immunosuppressive drug for preventing graft rejection and autoimmune disease. However, the therapeutic treatment induces several side effects such as nephrotoxicity, cardiotoxicity, hypertension, and hepatotoxicity. Curcumin has been successfully used as a potent antioxidant against many pathophysiological states. This experimental study was performed to test, during CsA treatment, the alterations of curcumin antioxidant properties against CsA-induced endothelial dysfunction. Rats were divided into four groups: control, curcumin alone, CsA, and CsA + curcumin; each group containing eight animals. The animals in the CsA + curcumin group were treated with CsA (10 days, 25 mg/kg, orally) and curcumin (15 days, 200 mg/kg, orally, starting 5 days before CsA administration). At the end of the treatments, the animals were killed; serum and aorta tissue were treated for biochemical and morphological analyses. The results indicate that CsA-induced aortic endothelial dysfunction was characterized by morphological and ultrastructural alterations in tissue architecture, changes in malondialdehyde and ferric reducing/antioxidant power levels, and increase in endothelial nitric oxide synthase and terminal-deoxynucleotidyl-transferase mediated dUTP nick end labeling (TUNEL) expression. In conclusion, our data suggest that the imbalance between production of free oxygen radicals and antioxidant defence systems, due to CsA administration, is a mechanism responsible for oxidative stress. Moreover, we show that curcumin plays a protective action against CsA-induced endothelial dysfunction and oxidative stress, as supported by biochemical, ultrastructural, immunohistochemical, and TUNEL results.